2021
DOI: 10.1051/e3sconf/202126305056
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Key global impacts on the construction industry and proposed coping strategies

Abstract: The construction industry is an essential tributary of the global economy and an important resource in the overall product of the local economies. In December 2019, the construction industry was exposed to a shock beyond the local level as a result of COVID-19, which was classified by the World Health Organization as a global pandemic after its rapid and sudden spread in multiple countries. The nature of the effects of COVID-19 on the construction industry varied according to the diversity of its projects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 7 publications
3
36
0
Order By: Relevance
“…the maximum responses were agreed to by 56 (37.34%), which mostly work in the field and private sectors. The obtained results agree with the published research by Husien et al (2021). Additionally, ILO (2021) confirms the yielded results from engineers in the present research.…”
Section: Covid-19 Causes Of Delays On Construction Projectssupporting
confidence: 93%
See 2 more Smart Citations
“…the maximum responses were agreed to by 56 (37.34%), which mostly work in the field and private sectors. The obtained results agree with the published research by Husien et al (2021). Additionally, ILO (2021) confirms the yielded results from engineers in the present research.…”
Section: Covid-19 Causes Of Delays On Construction Projectssupporting
confidence: 93%
“…This time the maximum answer was neutral (38%), but again, most of them were field engineers working in the private sector. Husien et al (2021) reported that the pandemic increased numerous challenges at the level of the workforce, low or halting productivity, and production time and costs. The current results agree with published work by Husien et al (2021).…”
Section: Covid-19 Causes Of Delays On Construction Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also explained how to use DT to manage disasters and risks related to the pandemic in the construction industry Zhou and Gheisari (2018). A recent study focused on the future directions of drone routing research, and the findings of this research have been used in many drone applications utilizing various models and kinds Husien et al (2021). In a scenario with a labor scarcity, it is essential to discover strategies to enhance construction sites' efficiency and lower the necessary labor force.…”
Section: Literature Review 21 Deployment Of Drone Technology In the C...mentioning
confidence: 99%
“…The world has been affected by crises such as Spanish Flu in 1918, Asian Flu in 1957, and Hong Kong Flu in 1968 during the last century, and Severe Acute Respiratory Syndrome -SARS in 2002, Swine flu in 2009, and Ebola in 2014 during near past (Vithana et al, 2020). COVID-19 is the prevailing crisis, announced as a pandemic by the World Health Organisation (WHO) and expeditious diffusion worldwide (Husien, et al, 2021). Kiraz and Ustun (2020) stated that the world had faced a critical situation where none could foresee its impact.…”
Section: Introductionmentioning
confidence: 99%